PENGARAUH PRODUK Dan PROMOSI TERHADAP KEPUTUSAN BERKUNJUNG SERTA DAMPAKNYA BAGI KEPUASAN W ISATAWAN DI BUMI PERKEMAHAN PLESERAN DUSUN NGLURAH - Suryo Adinugroho (Mount Hope Economic Global Journal, 2024)
Travelers can be motivated by a variety of things to visit a particular location or destination. In this case, decisions about products, promotions and visits are important components that contribute, or are expected, to visitor satisfact The objective of this study is to determine the impact of product md advertising on vinsiting decisions and its effect on tourist satisfaction at Pleseran campground, Tawanmagu. Quantitative methods were used to conduct the survey. The sample consisted of 95 tourists who were selected seem-a random at Pleseran Campground. Data was collected through surveys, and then tested and evaluated using path analysis and mediator (intervener) variables using SPSS. Data analysis results indicate that: (l) product has aitive and significant influence on visit decision and itsimpact on tourist satisfaction; (2) advertising has a g tive and significant influence on visit decision and its impact on tourist satisfaction; and (3) visit decision has a positive and significant influence on tourist satisfaction.